Lack of service delivery in the form of quality teaching and the secondary school learner migration - Modiba, N. S. (SAAPAM (South African Association of Public Administration and Management), 2016)
The paper critiques how persistent under-delivery of some secondary schools, orchestrate and trigger learner migration to better performing schools. The paper is both conceptual and empirical in nature. Document study and interviewing techniques were used to collect data from three selected secondary schools in one of the Districts of Limpopo Province. Research participants from whom data were generated included the school governors, members of the Representative Council of Learners and the School Management Team members. Research findings reveal that firstly, continuous excellent learner results, market a school. Secondly, that no single learner ever resists any good lesson in a school. Thirdly, that in any school, its learners serve as its own fundamental and dependable ambassadors in the wider community. Fourthly, that every school holds a key for its own greatness. As part of the conclusion, the researcher recommends that current public secondary school managers need to be instructional leaders par excellence, to continue to make their educational institutions schools of choices. Such a shift of focus and operation, is likely to enable schools to have a sustainable edge over their educational competitors.
Article published in: SAAPAM Limpopo Chapter 5th Annual Conference Proceedings, 2016
Keywords: Service delivery; Quality teaching; Learner migration; Teaching; Education, Secondary -- South Africa -- Limpopo; School management teams; High school students